(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article examines the advantages of taxation and the various factors influencing changes in the tax system. Through comprehensive analysis, the research aims to shed light on the significance of taxes and provide insights into how policymakers can adapt tax systems to meet evolving social needs.